2003
DOI: 10.1182/blood-2002-07-1989
|View full text |Cite
|
Sign up to set email alerts
|

T-cell clones can be rendered specific for CD19: toward the selective augmentation of the graft-versus-B–lineage leukemia effect

Abstract: Relapse of B-lineage acute lymphoblastic leukemia (B-ALL) after allogeneic hematopoietic stem cell transplantation (HSCT) commonly results from the failure of a graft-versus-leukemia (GVL) effect to eradicate minimal residual disease. Augmenting the GVL effect by the adoptive transfer of donor-derived B-ALL-specific T-cell clones is a conceptually attractive strategy to decrease relapse rates without exacerbating graft-versus-host disease (GVHD). Toward this end, we investigated whether a genetic engineering a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
207
0
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(212 citation statements)
references
References 63 publications
2
207
0
3
Order By: Relevance
“…The Bpep-CAR (44 kDa) in the expanded bulk and clone lines (lanes 2 and 3) is expressed at equivalent or greater levels than a CD19-specific scFvFc:zeta CAR (91 kDa) expressed by CTL clone E8 (lane 4). 11 The CD19R-chimeric immuno-receptor, previously developed in our laboratory, 11 sion above the isotype control (Figure 2b), confirming that the Bpep-CAR traffics to the cell surface of the genetically modified CTL.…”
Section: The Bpep-car Is Expressed By T Cells As a Cell-surface Transsupporting
confidence: 61%
“…The Bpep-CAR (44 kDa) in the expanded bulk and clone lines (lanes 2 and 3) is expressed at equivalent or greater levels than a CD19-specific scFvFc:zeta CAR (91 kDa) expressed by CTL clone E8 (lane 4). 11 The CD19R-chimeric immuno-receptor, previously developed in our laboratory, 11 sion above the isotype control (Figure 2b), confirming that the Bpep-CAR traffics to the cell surface of the genetically modified CTL.…”
Section: The Bpep-car Is Expressed By T Cells As a Cell-surface Transsupporting
confidence: 61%
“…The presence of 4-1BB in the chimeric receptor did not obstruct receptor expression and did not increase non-CD19- Two recent studies have shown that receptors composed of anti-CD19 scFv and CD3z endow T cells with the capacity to proliferate when mixed with CD19 þ cells and lyse CD19 þ targets in vitro and in vivo. 18,19 Brentjens et al 19 reported that T cells bearing such receptors could significantly improve the survival of immunodeficient mice engrafted with the Raji B-cell lymphoma cell line. Their results demonstrated the requirement for costimulation in T-cell-mediated antileukemic activity in vivo: only cells expressing the B7 ligands of CD28 such as Raji elicited effective T-cell responses.…”
Section: Discussionmentioning
confidence: 99%
“…In ALL, CD19 is an attractive target because it is expressed on virtually all leukemic cells in around 85% of cases (ie, B-lineage ALL), it is not expressed by normal nonhematopoietic tissues, and among hematopoietic cells, it is only expressed by Blineage lymphoid cells. [16][17][18][19] However, CD3z signaling may not be sufficient to produce a durable immune response; without a second signal, or costimulus, T cells rapidly undergo apoptosis after stimulation. [19][20][21][22] This is a central issue for T-cell therapy of ALL because ALL cells generally lack the ligands of CD28, 23 and of 4-1BB (C Imai, D Campana, unpublished observations), the two major T-cell costimulatory molecules.…”
Section: Introductionmentioning
confidence: 99%
“…ErbB2 is a cell surface growth factor receptor overexpressed on 30% of breast and ovarian cancers, but other single-chain antibody specificities exist with which it should be possible to target almost 100% of malignancies. [24][25][26][27][28][29][30] The immunotherapeutic application of this approach would involve the introduction of tumor-specific DCs into tumor-bearing hosts either alone to stimulate endogenous immune elements, or in combination with vaccines or adoptively transferred T cells that provide an enhanced number of antigen-specific T cells.…”
Section: Introductionmentioning
confidence: 99%